Variants of katG, inhA and nat genes are not associated with mutations in efflux pump genes (mmpL3 and mmpL7) in isoniazid-resistant clinical isolates of Mycobacterium tuberculosis from India. (December 2017) - Unissa, A. Nusrath; Dusthackeer, V.N. Azger; Kumar, Micheal Prem; Nagarajan, P.; Sukumar, S.; Kumari, V. Indira; Lakshmi, A. Ramya; Hanna, L.E.
Abstract: To understand the impact of efflux pump genes such as mmpL3 and mmpL7 on isoniazid (INH) resistance and to correlate with presence or absence of mutations in essential genes of INH resistance ( katG, inhA, and nat ) in clinical isolates of Mycobacterium tuberculosis ( M. tuberculosis ). One hundred (75 resistant and 25 sensitive) clinical isolates of M. tuberculosis from India were selected for the study. The presence of mutations in specific regions of katG, inhA, and nat, efflux pump genes ( mmpL3 and mmpL7 ) associated with INH resistance were analyzed using multiplex allele-specific polymerase chain reaction (MAS-PCR) and DNA sequencing methods, respectively. Substitution mutation AGC-ACC at codon 315 of the katG gene was detected in 65% of resistant isolates. Mutation (C-T at nucleotide position 15) in the inhA promoter region was seen in 22% of resistant isolates. Silent mutation (GGA to GGG) at codon 207 in the nat gene was found in three resistant isolates. No mutations were found in either of the efflux genes ( mmpL3 and mmpL7 ) in any of the isolates. Of the 75 resistant isolates analyzed, 74% had mutation in katG and inhA genes. Thus, this report suggests that the role of mmpL3, mmpL7 and nat genes in INH resistance should not be overestimated in comparison to the primary contribution by katG and inhA in clinical isolates of M. tuberculosis . Further, this concise report is the first of its kind to our knowledge, to show the influence of efflux genes on INH resistance in relation to katG and inhA in clinical isolates of M. tuberculosis .